KEPASTIAN HUKUM PENGAJUAN PEMBATALAN SERTIPIKAT TANAH YANG TELAH MELAMPAUI BATAS WAKTU (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 115 PK/PDT/2018) - Bodhi Alivian; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2020)
This article will analyze the legal certainty of submitting a cancellation of a land certificate that has been published for more than 5 years for holders of land rights whose names have been stated on the certificate. The purpose of land registration in Indonesia according to UUPA and PP 24/1997 is to provide legal certainty and protection for the certificate’s owner. Acticle 32 (2) PP 24/1997 provides assurance that the certificate that has been published above 5 years cannot be sued again and the plaintiff loses its right to sue. In fact, there have been lawsuits in public courts and state administrative courts that voided the validity of the certificates even though they have been published above 5 years, using the reason that they were contrary to law. The verdict will certainly give the view that UUPA and PP 24/1997 cannot provide the legal certainty and protection fot the certificate holders and give the anxious sense to the party whose names have been stated on the certificate because at any time can be submitted cancellation through court proceedings.